Product Development Strategy For Written Batik SMES In Sumberjo Sutojayan Village, Blitar District - Hery Suprayitno; Diana Elvianita Martanti (Metafora: Education, Social Sciences and Humanities Journal, 2023)
Batik Sum Gati is a labor-intensive business, so the production process is mostly carried out by human labor compared to machine power. This is done because the production process does not require special skills because the batik motifs have been designed by the owner of Batik Sum Gati. The purpose of this research is to find out the product development strategy for UMKM Batik Sum Gati in Sumberjo Village, Sutojayan District, Blitar Regency. The method used is a qualitative method with a descriptive type of research to analyze the development strategy of Batik SMEs (a case study on Batik Sum Gati in Blitar Regency). The type of technique used is a non-statistical data analysis technique which of course is descriptive qualitative. The results of this study are that Sum Gati Batik UMKM in developing their business uses 3 strategies, namely: (1) Cost leadership strategy; (2) differentiation strategy; (3) Focus strategy. Future research is expected to be able to analyze factors other than this research.